2023
DOI: 10.12688/f1000research.130038.1
|View full text |Cite
|
Sign up to set email alerts
|

Water-energy-food-ecosystem nexus and sustainable development in the Horn of Africa

Abstract: Water, energy and food (WEF) security are key indicators of sustainable development. Realization of sustainable development goals (SDGs) by countries is achieved through a water-energy-food-ecosystem nexus framework. Climate change is a threat to food, energy and water security in the Horn of Africa. The main aim of this review is to assess the status and prospects of WEF nexus as it relates to SDGs in the horn of Africa.  The countries considered were Ethiopia, Eritrea, Somalia and Djibouti. The review indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Further databases that are hosted by Organizations such as the World Bank, Food and Agriculture Organizations and World Food Programme were used. The search strategy utilized was adopted from Kanda et al [2023] in order to screen the relevant literature materials for use in this study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further databases that are hosted by Organizations such as the World Bank, Food and Agriculture Organizations and World Food Programme were used. The search strategy utilized was adopted from Kanda et al [2023] in order to screen the relevant literature materials for use in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Study conducted in Rwanda by Johnson and Axelsson [2017] while investigating the role of hydropower for the country's electrification plans revealed water insufficiency for the anticipated hydropower project plan as its expansion would lead to low water supply to cover the expected water demand in the country by 2026. Also the case study of Kenya explored similar trends observed in the SSA on the main factors contributing towards the deficiency of WEF like exponential population growth, extensive urbanization coupled with booming economy, and climate related vulnerabilities [Wakeford 2017;Okumu et al 2021;Awandu et al 2022a;Kanda et al 2023]. Mukuve and Fenner [2015] case study of Uganda analyzed beyond the WEF by incorporating the soil nutrient nexus into the mix for better understanding of the nexus ability in tackling the food insecurity.…”
Section: Focus Countriesmentioning
confidence: 99%
See 3 more Smart Citations